2016
DOI: 10.1088/0953-8984/28/31/315502
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of Mo1−xRexalloys studied through resonant photoemission spectroscopy

Abstract: Abstract.We have studied the electronic structure of Mo rich Mo 1−x Re x alloys (0≤ x ≤0.4) using valence band photoemission spectroscopy in the photon energy range 23-70 eV and density of states calculations. Comparison of the photoemission spectra with the density of states calculations suggests that with respect to the Fermi level E F , the d states lie mostly in the range 0 to -6 eV binding energy whereas s states lie in the range -4 to -10 eV binding energy. We have observed two resonances in the photoemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…Our studies revealed that the origin of the above observations is related to the phonon assisted interband s-d scattering between the band that newly appeared at the Fermi level (E f ) due to the ETT and the rest of the bands [8]. We have also shown from RPES studies on the alloys with x >> x C2 that the newly appeared band has Re5d like character [22]. Further analysis by Evans and Dowben revealed stronger Mo-Re orbital hybridization for x >> x C2 in comparison with the Mo-Mo or Re-Re bonding [36].…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Our studies revealed that the origin of the above observations is related to the phonon assisted interband s-d scattering between the band that newly appeared at the Fermi level (E f ) due to the ETT and the rest of the bands [8]. We have also shown from RPES studies on the alloys with x >> x C2 that the newly appeared band has Re5d like character [22]. Further analysis by Evans and Dowben revealed stronger Mo-Re orbital hybridization for x >> x C2 in comparison with the Mo-Mo or Re-Re bonding [36].…”
Section: Introductionsupporting
confidence: 52%
“…In this energy range, the photoemission spectra is more bulk sensitive [22]. Core levels were studied using X-ray photoemission spectroscopy (XPS) with Mg K α source (XR 50, SPECS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resonant photoemission intensities, found within 'Electronic structure of Mo 1−x Re x alloys studied through resonant photoemission spectroscopy', have implications beyond those discussed, by Sundar et al [1]. The suppression of the resonant photoemission intensities, as a functional of Mo 1−x Re x alloy composition [1], parallel similar trends to those found for Gd 1−x Ni x alloy films [2], and imply strong hybridization, considerable short-range in the Mo 1−x Re x alloy system.…”
mentioning
confidence: 78%